Host and Microbial Tryptophan Metabolic Profiling in Multiple Sclerosis - Gaetani, Lorenzo; Boscaro, Francesca; Pieraccini, Giuseppe; Calabresi, Paolo; Romani, Luigina; Di Filippo, Massimiliano; Zelante, Teresa (Frontiers in Immunology, 2020)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS), associated with demyelination and neuronal loss. Over the last years, the immunological and neuronal effects of tryptophan (Trp) metabolites have been largely investigated, thus leading to hypothesize a possible involvement of these compounds and the related enzymes in the pathophysiology of MS. Specifically, the kynurenine pathway of Trp metabolism is responsible for the synthesis of intermediate products with potential immunological and neuronal effects. More recently, Trp metabolites, originating also from the host microbiome have been identified in MS and it has been shown that they are differently regulated in MS patients. Here, we sought to discuss whether in MS patients a specific urinary signature of host/microbiome Trp metabolism can be potentially identified to select novel biomarkers and guide towards the identification of specific metabolic pathways as drug targets in MS.